Dominium and The Empire of Laws - Stewart, Fenner L. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
Civic republicanism endorses a freedom ideology that can support the corporate social responsibility movement [CSR] in some of the challenges it faces. This article is a call for CSR to embrace this normative guidance as a superior alternative to mainstream liberalism. Part I is the introduction. Part II discusses the institutional changes that gave rise to CSR’s present incarnation. Part III builds upon this discussion, explaining how corporate risk management strategies pose a threat to CSR’s persuasive authority today. It then considers CSR’s options for enhancing governance when such persuasive authority is not available. It determines that inspiring integrity – above all else – is integral to success and that, in turn, the removal of moral distance is key to inspiring such integrity. It also notes that whether a form of coercive authority exists or not to back a governance mechanism, the removal of moral distance will be key to its effectiveness. Part IV notes that efforts to remove moral distance have been attempted since the 1970s, but time has proven that business actors have been resilient to meaningful change. It argues that this failure to reduce moral distance is, in part, the result of mainstream liberalism, which continues to nullify such efforts to make business actors feel more accountable for the impacts of their decision-making. It then explores liberalism, detangling the meaning of possibly the most contested, and normatively powerful, concept from the twentieth century to the present. Part V explains civic republicanism. It then explores civic republicanism’s conceptual proximity to liberalism. Part VI makes the case for why civic republicanism ought to amend the liberal message, recasting the rights and responsibilities of both imperium (that is, the authority of the sovereign) and dominium (that is, the private authority usually emanating from property and contract) within society. Part VII concludes with a short reflection on the ground covered.